Fish community in Pengkalan Gawi - Pulau Dula section of Kenyir Lake, Terengganu, Malaysia - Kamaruddin, Izharuddin Shah; Abdul Satar, Mustafa Kamal; Christianus, Annie; Daud, Siti Khalijah; Abit, Lirong Yu (Universiti Malaysia Terengganu Publisher, 2011)
A study of species diversity offish population was carried out at Pengkalan Gawi- Pulau Dula section of Kenyir Lake, Terengganu. Fish sampling at three (3) stations was conducted monthly from February 2008 to January 2009 using gill nets. A total of 274 fishes from 13 species were collected in this study. The most abundant fish species collected were Barbodes schwanenfeldii (Lampam Sungai) (35.77 %), followed by Notopterus sp. (Belida) (27.37 %) and Hampala macrolepidota (Sebarau) (16.06 %). The other species identified in this study were Hemibagrus nemurus (Baung) (8.03%), Channa micropeltes (Toman) (4.4%), Pristolepis faciatus (Patong) (3.65%), Cyclocheilichthys apogon (Temperas) (1.46%), Osteochilus hasselti (Terbol) (1.09%), Osteochilus vitatus (Rong) (0.73%), Chela anomalura (Lalang) (0.36%), Labiobarbus lineatus (Kawan) (0.36%), Channa striatus (Haruan) (0.36%) and Probarbus jullieni (Temoleh) (0.36%). The Shannon-Weaver index showing the fish diversity index was 1.71, Pielou's Evenness index was 0.66 and Margalef's Species Richness index was 4.92 respectively. Most of the species found in this study were similarly reported in other studies in Kenyir Lake. It is hoped that the results of this study will be useful in contributing towards the management of the lake in a sustainable manner for future generations.